Fourier Transform Infrared Spectroscopy Analysis of Seagrass Polyphenols - Ragupathi Raja Kannan, Rengasamy; Arumugam, Rajasekaran; Anantharaman, Perumal (Current Bioactive Compounds, 2011)
The application of IR spectroscopy in herbal analysis is still limited when compared to other areas (food and beverage industry, microbiology, pharmaceutical etc). The aim of this work is to adopt the fingerprinting through Fourier Transform Infrared (FTIR) technique to measure the polyphenols of six seagrasses of Gulf of Mannar, India. The representative IR spectra from the mid-infrared region (4000-400 cm-1) for aqueous methanolic extract of seagrasses were observed. Samples of six seagrasses in the region of polyphenols showed slight variation in bands than the standards. Noticeably the presence of wavelength numbers of FTIR spectra of Gallic acid at 669, 763, 1025, 1100 and 1654 cm-1, Tannic acid at 669, 860, 1172, 1511 and 1627 and p-Coumaric acid at 669, 1124, 1171, 1508 and 1638 cm-1 were also observed in all seagrasses analysed. Wavelength FTIR spectra corresponding for Vanillin was 668, 1498, 1534, 1617, 1654 and 3392 cm-1, among them 668 cm-1 is present in all the seagrass and 1498, 1534, 1617 and 1654 cm-1 were present in H. pinifolia alone. This is the first study that proves FTIR technique is an efficient tool for measuring polyphenols in seagrasses.
Keywords: spectroscopy